Fuzzy String Matching Using a Prefix Table - Kostanyan, Armen H. (Mathematical Problems of Computer Science, 2021)
The string matching problem (that is, the problem of finding all occurrences of a pattern in the text) is one of the well-known problems in symbolic computations with applications in many areas of artificial intelligence. The most famous algorithms for solving it are the finite state machine method and the Knuth-Morris-Pratt algorithm (KMP). In this paper, we consider the problem of finding all occurrences of a fuzzy pattern in the text. Such a pattern is defined as a sequence of fuzzy properties of text characters. To construct a solution to this problem, we introduce a two-dimensional prefix table, which is a generalization of the one-dimensional prefix array used in the KMP algorithm.